Artificial intelligence and soft computing. 15th International Conference, ICAISC 2016, Zakopane, Poland, June 12-16, 2016, Proceedings /: 15th International Conference, ICAISC 2016, Zakopane, Poland, June 12-16, 2016, Proceedings. Part I : (2016) - Unknown
No abstract available